Duolingo and The Development of Speaking Skills: A Case Study - Frans, Nofry; Wahani, Vera; Baureh, Gabriella A,D (Universitas Pahlawan Tuanku Tambusai, 2025)
English‘s a crucial productive skill in global communication because it enables verbal interaction. Developing English speaking skills presents challenges, including shyness, limited opportunities for practice, and limited use of learning media that support active speaking practice. This study aims to investigate the effect of Duolingo use on the development of English speaking skills among English language students at Klabat University in the second semester of the 2024/2025 academic year. The research method used a mixed method, namely quantitative and qualitative research. The results provide evidence that Duolingo features can significantly help or challenge English speaking skills. Furthermore, the Duolingo application has contributed significantly to the development of students' communicative competence in English at Klabat University. However, the Duolingo application didn’t significantly impact student self-confidence. This’s evidenced by students' pedagogical recommendations regarding the need for improvement in Duolingo use, including the need for two-way features, evaluation and feedback features, and improvements to the Duolingo application.